Oil Costs and Prices: An Empirical Causality Analysis - Moreno Alonso, Pedro; MuÃ±oz San Roque, Antonio (International Journal of Energy Economics and Policy, 2021)
This study analyzes the causal relationship between oil prices and production costs and their implication over hedging in production companies. Two different data sets have been used as a proxy for production costs: i) monthly product price index related to oil activities from the Bureau of Labour of Statistics; ii) yearly data obtained from reports of publicly traded oil companies. For the oil price, different future contracts of Brent (1M, 12M, 24M, 60M) have been explored. Based on Granger’s definition of causality, and using the Toda-Yamamoto (1995) methodology, both causal directions have been tested. The results obtained indicate that oil prices (any term of the curve) Granger-cause production costs, and not the other way around (as it has been considered for many specialists) in any term of the curve. Keywords: Oil Price, Production Costs, Hedging, Granger Causality, Toda-Yamamoto JEL Classifications: Q41, Q47 DOI: https://doi.org/10.32479/ijeep.10887